Using Professional Standards : Assessing Work Integrated Learning in Initial Teacher Education : Final Report. - Sim, Cheryl; Freiberg, Jill; Allard, Andrea; White, Simone; Le Cornu, Rosie; Cater, Briony (Office for Learning and Teaching, 2013)
Final report from a collaborative project led by Griffith University with Deakin University, Monash University and University of South Australia that endeavoured to develop clear and explicit descriptions of evidence of achievement of professional 'standards' that reflected high academic standards within the field of teacher education at undergraduate level. The project aimed to enhance both the validity and reliability of assessment of the work integrated learning (WIL) component of preservice teacher education programs across Australia. The project produced a website providing teacher educators across Australia access to inventories of performance expectations and exemplars including video clips to inform the assessment of initial teacher education students in the workplace. The project set out to provide answers to the following questions:- How do practising teachers make their judgements about preservice teachers under their supervision?- What is the shared knowledge that supervising teachers bring to these judgements?- How can this knowledge be systematised to ensure consistency of judgements across the different stages of preservice WIL and help preservice teachers meet specific professional standards? The project had three specific goals: 1. A set of recommendations for Higher Education specifically teacher education to build effective communities of practice between Higher Education Institutions and teachers. Three (3) exemplar 'Communities of Practice' were established for the duration of the project in three states that became the means for on-going collaborative discussions to emphasise the importance of making consistent evidence-based judgements to ensure reliable assessments of preservice teachers in the school context. An inventory of the specific performance criteria and standards documented and explicated by expert supervising teachers' communities of practice: performance criteria and standards that constituted evidence of three levels of achievement (high, satisfactory and limited) of professional standards for preservice teachers at three stages (early, middle and final) of preservice teachers' professional experiences. A professional learning package consisting of a website, video clips and elaborated inventories that inform the assessment of initial teacher education students for all teacher educators in the workplace at (a) three stages (early, middle and final) of preservice teachers' professional experiences for (b) three levels of achievement (high, satisfactory and limited). The TeamSix experienced teacher educators representing three states formed the project team. Each had specific responsibilities and worked closely with supervising teacher participants at all stages of the project. Each team member became a member of at least one community of practice established for the project. Each State team(Queensland, Victoria and South Australia): (i) Established their CoRP (Communities of Reflective Practitioners) (ii) Organised and managed the four workshops for their respective State (iii) Audio-taped the workshops (iv) Critically reviewed, as peer teams, the outcomes of each workshop as the project progressed. This project was specifically focused on the professional learning and assessment practices in the WIL component of teacher preparation. It sought to contribute to the development of shared understandings of the practices among school teachers, preservice teachers and higher education academics in teacher education programs.